The Impact of Foreign Debt on Economic Growth in Developing Countries - Ary Andrian; Mohamad Halilintar (Kajian Ekonomi dan Akuntansi Terapan, 2026)
This study examines the relationship between external debt and economic growth in developing countries, focusing on six ASEAN countries during the period 2015–2024. Developing countries often face limited domestic savings and foreign exchange constraints, which encourage them to rely on external debt as a source of development financing. This research aims to test the validity of the dual gap model and the debt overhang hypothesis in explaining the impact of external debt on economic growth. The study employs panel data regression analysis using the Random Effects Model (REM). The variables analyzed include external debt, exports, labor force, inflation, and economic growth. The findings reveal that external debt has a non-linear relationship with economic growth. External debt contributes positively to economic growth when maintained below a certain threshold, estimated at approximately 50% of GDP. However, once external debt exceeds this threshold, its impact becomes negative and hinders economic growth, supporting the debt overhang hypothesis. In addition, exports and labor force are found to have positive and statistically significant effects on economic growth, while inflation negatively affects economic performance. These findings indicate that external debt can be an effective instrument for promoting economic growth if managed productively and sustainably. The study provides important policy implications for developing countries, particularly ASEAN economies, emphasizing the need for prudent debt management policies, efficient allocation of borrowed funds, and macroeconomic stability to optimize the benefits of external debt while minimizing the risks of excessive debt burdens and financial instability.